Observation of Reading to Learn Model in Science Materials in Grade VIII of SMP Negeri 2 Kota Solok - Ananda, Aisyah Salsabila Dwi; Muttaqiin, Arief (Department of Science Education, 2024)
This study aims to determine the implementation of Reading to Learn learning on science material for class VIII SMP Negeri 2 Kota Solok. This research is quantitative descriptive. The data collection technique in this study used observation sheets on the implementation of learning which were filled in by observers during the learning process. Based on the results of the observational analysis, it shows that the implementation of the Reading to learn learning model as a whole has been going very well. This is shown from the proportion of implementation of each syntax of the R2L model. At the reading preparation stage, it was obtained that the proportion of execution was 100%, reading details was 75%, note-taking was 83.3% and joint construction was 100%. The percentage of each R2L model syntax is included in the good and very good criteria.